Mechanical properties and microstructure of basalt fibre and nano-silica reinforced recycled concrete after exposure to elevated temperatures. (30th June 2020) - Yonggui, Wang; Shuaipeng, Li; Hughes, Peter; Yuhui, Fan
Highlights: Elevated temperature performance of recycled concrete (RC) were studied. Nano-silica (NS) and basalt fiber (BF) can improve the mechanical properties of RC. Degradation mechanisms of RC with NS and BF were examined by SEM and XRD analysis. The splitting tensile strength has a linear relationship with the compressive strength. Abstract: In this study, basalt fibre and nano-silica were used to reinforce recycled concrete, to enhance the elevated temperature performance of the recycled concrete and expand its application space. The mechanical properties and microstructures at 25, 200, 400, and 600 °C were studied using a static load test, scanning electron microscopy and X-ray diffraction. The results indicate that with an increase in temperature, the compressive strength and splitting tensile strength decrease, the mortar matrix gradually loosens, the properties of the interface transition zone and the bonds of the mortar to the fibres deteriorate, the influence of the replacement ratio on the compressive strength is weakened, and the influence of the nano-silica on the compressive strength is enhanced. At elevated temperatures, basalt fibre is beneficial to the improvement of the compressive strength of the recycled concrete, and basalt fibre has a more significant effect on the splitting tensile strength than the replacement ratio and nano-silica content. The relative residual splitting tensile strength increases as the basalt fibre content increases. Nano-silica is generally beneficial to the improvement of the compressive strength at different temperatures. The results indicate that basalt fibre and nano-silica contribute to the improvement of the interface transition zone performance and to the elevated temperature performance of the recycled concrete.